Experimental and numerical study on Mode I and Mode II interfacial fracture toughness of co-cured steel-CFRP hybrid composites. (January 2022) - Yao, Youqiang; Shi, Pengcheng; Chen, Mingda; Chen, Gang; Gao, Cong; Boisse, Philippe; Zhu, Yingdan
Abstract: Interfacial fracture toughness of co-cured steel-carbon fiber reinforced plastic (CFRP) hybrid composites were investigated in this paper. To illustrate the effect of the interlayer on the fracture toughness, steel-CFRP hybrid composites were prepared by different manufacturing processes based on steel surface treatment (abrasion or grit blasting) and adhesive-bonding process. The experimental results of double cantilever beam (DCB) tests and end notched flexure (ENF) tests demonstrate that, the Mode I and Mode II interfacial fracture toughness of the hybrid composites can be improved by using a grit blasting surface treatment on steel and introducing an adhesive layer at the steel/CFRP interface. The hybrid composites mainly show fiber/epoxy interfacial failure of CFRP under Mode I loading conditions, while it mostly exhibits adhesive failure of steel/CFRP interface under Mode II loading condition. Moreover, the interfacial tensile strengths of steel-CFRP hybrid composites are predicted by finite element analysis, and both experimental and numerical results confirm the improvement of interfacial fracture toughness.